PENGARUH KOMPETENSI MANAJERIAL KEPALA MADRASAH, BUDAYA MADRASAH DAN DISIPLIN KERJA GURU TERHADAP MUTU MADRASAH IBTIDAIYAH DI KABUPATEN KENDAL - Nura Azizah; Ngasbun Egar; Rasiman (STKIP Subang, 2023)
Madrasah quality is data and information, quality includes: a. educational results; b. educational content; c. educational process; d. educational assessment; e. teachers and education personnel; f. educational infrastructure; g. education financing; and h. education management. The aims of this study were: 1) to find out the influence of the madrasa head's managerial competence on the quality of the madrasah primary school. 2) determine the magnitude of the influence of madrasa culture on the quality of madrasas. 3) knowing the magnitude of the influence of the teacher's work discipline together on the quality of Islamic elementary schools. 4) knowing the magnitude of the influence of the managerial competence of the madrasah head, madrasa culture and teacher work discipline together on the quality of the madrasah primary school. The population of this study was 263 MI NU teachers in Kendal Regency. A sample of 159 teachers was taken by proportional random sampling. Data collection by questionnaire. Data analysis techniques with descriptive data analysis, prerequisite tests which include normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests and hypothesis tests include simple and multiple linear regression. The results showed that: 1) the managerial competency of the madrasah principal affected the quality of the Madrasah 81.1% with the regression equation Ŷ = 11,190 + 0.781X1 with a correlation coefficient of 0.901. 2) Madrasah culture affects the quality of Madrasahs by 75.6% with the regression equation Ŷ = 8.685 + 0.740 X2 with a correlation coefficient of 0.869. 3) Teacher work discipline affects quality by 81.8% with the equation Ŷ = 11.942 + 0.743 X3 with a correlation coefficient of 0.905. 4) Madrasah Principal Managerial Competence, madrasa culture and work discipline have an effect on Madrasah quality by 91.22% with the equation Ŷ = 1.386 + 0.184 X1 + 0.381 X2 + 0.395 X3. Then the value of the correlation coefficient r is equal to 0.910. Based on the research results, it is recommended that the head of the madrasa conduct guidance and direction to teachers, especially so that they can improve and develop madrasa management, then teachers can also attend training and seminars so that they can improve work discipline and work culture so that the quality of madrasas can increase. Madrasah heads can reflect and self-evaluate by increasing competence in leadership and managerial by making administrative arrangements and structured management.